ANALISIS POTENSI LEGALISASI EUTANASIA DI INDONESIA : DISKURSUS ANTARA HAK HIDUP DENGAN HAK MENENTUKAN PILIHAN - Xavier Nugraha; Sabdo Adiguno; Shintya Yulfa; Yuni Lathifah (University Of Bengkulu Law Journal, 2021)
The problem of euthanasia has existed since the health community was facing an incurable disease, while the patient was already dying and torturing. In such situations, it is not uncommon for patients to beg for relief from this suffering and do not wish to have their life extended. This is where the term euthanasia appears, which is letting go of one's life in order to be free from suffering or to die properly. This study aims to determine the concept of freedom to live, human freedom to choose and review legal norms in Indonesia and several other countries. However, in its application there is a dilemma, which is considered contrary to the right to life if euthanasia is carried out. This research is a legal research with an approach obtained by examining library materials or secondary data or what is called normative legal research or literature law research. The approach in research uses aConceptual Approach, which is an approach that departs from the views or doctrines that develop in legal science to build legal arguments when solving legal issues at hand. From this legal research study, it can be concluded that the presence of euthanasia is considered a human right in the form of the right to die which is considered to bring happiness and pleasure to him. Eutanasia when viewed from the aspect of criminal law and human rights in Indonesia are still having a debate that has not found the end, for the provision of human rights by the opposition national laws, especially the Criminal Code so there needs to be development of the law on regulation of euthanasia in Indonesia by taking into account medical factors normative.